Orphan Child Maintenance in Islamic Law: Contemporary Social Relevance and a Case Study of Medan Tembung District - Heriandi; Yazid, Imam; Lubis, Junaidi (Al-Risalah, 2026)
This article examines the formulation and implementation of the obligation to provide maintenance for orphans in Islamic law and the factors contributing to its variation and neglect in social practice. The main research problem addresses how Islamic law normatively constructs the obligation of orphan maintenance and why this norm is not fully internalized in community life. This study employs an empirical legal research method with a socio-legal approach, integrating normative analysis of the Qur’an, hadith, and classical Islamic jurisprudence with field research conducted in Medan Tembung District through interviews, observation, and documentation. The findings reveal that Islamic law provides a strong and multilayered normative framework for ensuring orphan maintenance through the responsibilities of guardians, extended family, and social mechanisms; however, in practice, maintenance is predominantly perceived as a moral or charitable act rather than a legally binding obligation. Variations and neglect are influenced by economic constraints, low legal awareness, family cultural structures, and weak institutional integration. The study concludes that the gap between normative provisions and social practice undermines effective protection of orphans’ welfare, highlighting the need to strengthen legal awareness and develop a more structured and sustainable system of maintenance responsibility.